ULTRASOUND-ASSISTED ADSORPTION HG (II) USING KAOLIN ADSORBENTS MODIFIED WITH ANIONIC SURFACTANT - Putra, Alfian; Zaimahwati; Syahyadi, Rizal; Rihayat, Teuku; Dewi Astuti, Rima Dhinta; Izzati, Isra Adelya Izzati (International Journal of Research -GRANTHAALAYAH, 2022)
This study aims to test the reservoir wastewater containing domestic waste using a modified kaolinite adsorbent with Alkyl Benzene Sulfonate surfactant using ultrasonic technology (KM). First, the adsorbent to be used is characterized using several different techniques such as SEM analysis, and FTIR and the calculation of the efficiency of the adsorbent concerning contact time with wastewater. Meanwhile, the wastewater tested was tested for the effect of contact time on TDS and PH. The results of the analysis show that the maximum waste reduction efficiency occurs in modified kaolin (KM), where adsorption occurs faster than in unmodified natural kaolin (PK). The maximum percentage is 84, 21% for metal removal efficiency using modified kaolin at a contact time of 45 minutes and a weight of 1.8 g of adsorbent, while kaolin without modification has an efficiency of 62.47% at a contact time of 80 minutes and a weight of 1.8 g of adsorbent. The contact time test on the TDS value of wastewater that has been adsorbed with KM shows that the TDS value is getting lower over time, which indicates the Hg (II) ion has been dispersed and fused so that the Hg (II) metal in the water is reduced. The use of the adsorption method with the help of ultrasonic technology is proven to be more efficient in accelerating the removal of Hg (II) ions by increasing the surface dispersion of the adsorbent with metal ions in water. The contact time test on the TDS value of wastewater that has been adsorbed with KM shows that the TDS value is getting lower over time, which indicates the Hg (II) ion has been dispersed and fused so that the Hg (II) metal in the water is reduced. The use of the adsorption method with the help of ultrasonic technology is proven to be more efficient in accelerating the removal of Hg (II) ions by increasing the surface dispersion of the adsorbent with metal ions in water. The contact time test on the TDS value of wastewater that has been adsorbed with KM shows that the TDS value is getting lower over time, which indicates the Hg (II) ion has been dispersed and fused so that the Hg (II) metal in the water is reduced. The use of the adsorption method with the help of ultrasonic technology is proven to be more efficient in accelerating the removal of Hg (II) ions by increasing the surface dispersion of the adsorbent with metal ions in water.